Media education and the problem of circulating false information through social networks - dahhmani, fatima; dahmani, mohamed (Journal of Social Sciences and Humanities, 2024)
The study aimed to reveal the role of media education in addressing the problem of the circulation of false information through social media networks in the study sample ", and we have relied on the descriptive methodology, and the investigators' data have been collected through electronic identification distributed to 100 users according to the method of the intentional random sample after verifying its veracity and consistency, which has made it possible to reach important results: 45% of the sample individuals consider that the concept of media education lies in the ability to use positive and safe media. 67% of researchers stated that media education is based on the skill of understanding and interpreting media messages and discovering their values. In addition, 94% of researchers were exposed to false information on Facebook's social media sites. More than 65% of users apply the skill of analyzing, reading and understanding information to benefit from and share it with others that 19% of sample members consider that the inclusion of media education is in the curriculum.